Analysis of Problems in Identifying Psychosocial Impacts in Environmental Impact Assessment (EIA) Studies - Rozali Fathar, Imam; Rusdiyanto, Edi (PT. Publikasiku Academic Solution, 2026)
Environmental Impact Analysis (AMDAL) in Indonesia has historically prioritized biogeophysical parameters, thereby neglecting psychosocial dimensions that are critical determinants of public health. This neglect is urgent, as environmental changes from development projects can trigger psychological distress, social conflict, and erosion of community well-being—impacts that remain largely unrecognized within the current regulatory framework. This article aims to analyze the epistemological and methodological challenges in identifying psychosocial impacts in AMDAL and to propose an integrative framework based on Health Impact Assessment (HIA). Using a qualitative literature-based approach with content and thematic analysis, this study examined scientific publications, policy documents, and international guidelines. The findings reveal that psychosocial impacts are latent, multifactorial, and difficult to quantify within the dominant positivist paradigm, resulting in their systematic underrepresentation in AMDAL documents. The study concludes that integrating HIA, psychometric instruments, and participatory methods can strengthen AMDAL as a more comprehensive policy tool for safeguarding both environmental quality and community well-being.